Minat Belajar Siswa dengan Variasi Penggunaan Media Pembelajaran (Survey pada Siswa Jurusan Akuntansi di SMK Negeri 3 Bandung) - Leni Maryani; Veri Aryanto Sopiansah (Institut Pendidikan Indonesia, 2019)
The purpose of this study was to determine (1) how perceptions of students about the variety of instructional media, (2) the effect of variations in the use of instructional media on student interest accounting department at SMK Negeri 3 Bandung. The method used is survey with a student sample of the accounting department at SMK Negeri 3 Bandung. Analysis of the data used is the analysis of the data verification through calculation of average (mean) score for solving the first problem. As for solving the problem are both used a simple linear regression analysis. Results of research on the variations of the use of learning media can be summed variety of instructional media usage